Bacterial Diversity in the Hyperalkaline Allas Springs (Cyprus), a Natural Analogue for Cementitious Radioactive Waste Repository. Issue 2 (7th February 2016) - Rizoulis, Athanasios; Milodowski, Antoni E.; Morris, Katherine; Lloyd, Jonathan R.
Abstract : The biogeochemical gradients that will develop across the interface between a highly alkaline cementitious geological disposal facility for intermediate level radioactive waste and the geosphere are poorly understood. In addition, there is a paucity of information about the microorganisms that may populate these environments and their role in biomineralization, gas consumption and generation, metal cycling, and on radionuclide speciation and solubility. In this study, we investigated the phylogenetic diversity of indigenous microbial communities and their potential for alkaline metal reduction in samples collected from a natural analogue for cementitious radioactive waste repositories, the hyperalkaline Allas Springs (pH up to 11.9), Troodos Mountains, Cyprus. The site is situated within an ophiolitic complex of ultrabasic rocks that are undergoing active low-temperature serpentinization, which results in hyperalkaline conditions. 16S rRNA cloning and sequencing showed that phylogenetically diverse microbial communities exist in this natural high pH environment, including Hydrogenophaga species. This indicates that alkali-tolerant hydrogen-oxidizing microorganisms could potentially colonize an alkaline geological repository, which is predicted to be rich in molecular H2, as a result of processes including steel corrosion and cellulose biodegradation within the wastes. Moreover, microbial metal reduction was confirmed at alkaline pH in this study by enrichment microcosms and by pure cultures of bacterial isolates affiliated to the Paenibacillus and Alkaliphilus genera. Overall, these data show that a diverse range of microbiological processes can occur in high pH environments, consistent with those expected during the geodisposal of intermediate level waste. Many of these, including gas metabolism and metal reduction, have clear implications for the long-term geological disposal of radioactive waste.